Exciton Delocalization and Transport in Photosystem I of Cyanobacteria Synechococcus elongates: Simulation Study of Coherent Two-Dimensional Optical Signals - Abramavicius, Darius (2009)
Electronic excitations and the optical properties of the photosynthetic complex PSI are analyzed using an effective exciton model developed by Vaitekonis et al. [Photosynth. Res. 2005, 86, 185]. States of the reaction center, the linker states, the highly delocalized antenna states and the red states are identified and assigned in absorption and circular dichroism spectra by taking into account the spectral distribution of density of exciton states, exciton delocalization length, and participation ratio in the reaction center. Signatures of exciton cooperative dynamics in nonchiral and chirality-induced two-dimensional (2D) photon-echo signals are identified. Nonchiral signals show resonances associated with the red, the reaction center, and the bulk antenna states as well as transport between them. Spectrally overlapping contributions of the linker and the delocalized antenna states are clearly resolved in the chirality-induced signals. Strong correlations are observed between the delocalized antenna states, the linker states, and the RC states. The active space of the complex covering the RC, the linker, and the delocalized antenna states is common to PSI complexes in bacteria and plants.